Fracture regularity of corn kernel and stalk based on fractal theory - Li, Xinping; Wang, Junyi; Li, Yanan; Xu, Shendi; Hou, Jiarui (International Journal of Agricultural and Biological Engineering, 2025)
Since the fracture property of corn stalk determines the difficulty for corn to fall off, it is of great significance to study the fracture law of the corn stalk with high water content and explore the corn threshing method without causing great damage. Taking two varieties of corn as the research object, this study carried out single and multi-angle corn stalk fracture tests to explore the changes in the linkage between stalk and corn kernel at different positions as well as under different application modes and angles. The results showed that the force required for radial stretching was the greatest. Moreover, the fracture mechanics model of corn stalk was established to measure the fracture toughness of corn stalk. The peak value of critical load PQ load displacement curve (FMAX) was indicated. Based on the fractal theory, the fractal characteristics of the fracture surface of the stalk at different positions of the ear were analyzed, and the fractal dimension was calculated using the islet method. The findings indicated that the larger the fractal dimension of the fracture surface on the corn stalk, the more energy consumed in the fracture of corn stalk. These findings can be further utilized to explore the performance of corn kernel and reveal the fracture rule of corn kernel and stalk to identify the optimal form of force to make corn kernels fall off the corn cob and provide the theoretical basis for reducing the loss caused in the falling process of corn kernel. Keywords: corn kernel, force of connection, fracture law, fractal characteristics, fractal dimension DOI: 10.25165/j.ijabe.20251803.9222 Citation: Li X P, Wang J Y, Li Y N, Xu S D, Hou J R. Fracture regularity of corn kernel and stalk based on fractal theory. Int J Agric & Biol Eng, 2025; 18(3): 37–43.